The Monophthongisation of Diphthongs Before Dorsal Fricatives: A Corpus Study - Wełna, Jerzy (Studia Anglica Posnaniensia, 2010)
The paper discusses the geographical distribution of the monophthongisation of (1) the diphthong [ei] (< [e:ç]) before the palatal fricative [ç] (i.e. [eiç > i:ç]) and (2) the diphthong [ou] (< [o:×]) before the velar fricative [×] (i.e. [oux > u:x] in words like high an bough. The resulting monophthongs became the input to the diphthongisation rule, a part of the Great Vowel Shift. On the basis of forty-nine Middle English poetic texts from the Chadwyck-Healey online corpus an effort is made here to establish temporal and dialectal conditioning of the change.